2007
DOI: 10.1007/s10669-007-9006-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioremediation on the growth of Okro (Abelmoshus esculetus) in the Niger Delta soils

Abstract: This paper communicates the effect of bioremediation on the performance of Okro plant (Abelmoshus esculentus) in a typical Niger Delta soil that has received 5% crude oil pollution level. Biodegrading bacteria such as Pseudomonas fluorescen, Acinetobacteria iwofii, Bacillus subtilus, Arthrobacter globiformis that was isolated from previously polluted soils was introduced into the samples. The treatment combinations are as follows (A) = control without crude oil; B = soil + crude oil, (C) = soil + crude oil + m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…Similar observations drocarbon utilizing bacterial and Hydrocarbon utilizing fungal counts in the various treatments setups (Figs.13-14). The result is consistent with the reports of [17], Nrior and Mene, [21] and Ogbonna et al [23] who observed that Total rotrophic Bacterial and Hydro-carbon Utilizing Bacterial counts increased over time in a nutrient amended crude oil contaminated soil undergoing bioremediation with time.…”
Section: 11supporting
confidence: 93%
See 2 more Smart Citations
“…Similar observations drocarbon utilizing bacterial and Hydrocarbon utilizing fungal counts in the various treatments setups (Figs.13-14). The result is consistent with the reports of [17], Nrior and Mene, [21] and Ogbonna et al [23] who observed that Total rotrophic Bacterial and Hydro-carbon Utilizing Bacterial counts increased over time in a nutrient amended crude oil contaminated soil undergoing bioremediation with time.…”
Section: 11supporting
confidence: 93%
“…12) was observed to show a similar pattern as THB on day 7 and day 56 with contaminated soil+ goat manure + fish waste revealing the highest value on day 56. Similar observations were observed in the Hydrocarbon utilizing bacterial and Hydrocarbon utilizing fungal counts in the various treatments setups (Figs.13 The result is consistent with the reports of Chikere et al [17], Nrior and Mene, [21] and Ogbonna et al [23] corresponding bioremediation with time in the bio stimulated soil compared to the controls for both 5% and 10% crude oil contaminated soil (Figs. ained from day 7 to 56 ranged in the respective experimental plots as follows; Total Heterotrophic Bacteria ranged from CFU/g (control) < 6.32 to 9.05 CFU/g (CS+FW) < 6.41 to 9.13 Log 10 CFU/g (CS+GM) < 6.32 to 9.58 Log 10 CFU/g M).Similar progression was observed fungi, Hydrocarbon utilizing bacteria and Hydrocarbon utilizing fungi in all experimental setup except for the control setups The Total Heterotrophic Fugal count (Fig.…”
Section: 11supporting
confidence: 91%
See 1 more Smart Citation
“…That is why various authors have studied the effects of soil contamination on seed germination, (Adam andDuncan, 1999, 2002;Banks and Shultz, 2005;Agbogidi et al, 2006;Ogbonna et al, 2007), however, there are very few that have looked at tree species. Adam andDuncan (1999, 2002) investigated the effects of diesel oil on the growth of various plants, including grass, leguminous and cultivated species.…”
Section: Resultsmentioning
confidence: 99%
“…Yet the area of the eophylls (60 days) in the contaminated soil was greater than in the uncontaminated soil ( Figure 6). Ogbonna et al (2007), studied the effect of bioremediation and crude oil-contamination of soil on the growth of Abelmoschus esculentus (L.) Moench. They concluded that when microorganisms and fertilizers are added to the crude oil-contaminated soil, the plants exhibited a greater number of leaves, greater biomass, a higher percentage of germination and a high percentage of degradation of hydrocarbons present in the soil, when compared to the treatments that were not subjected to bioremediation.…”
Section: Resultsmentioning
confidence: 99%